Analysis of the Financial Performance of the South Sulawesi Provincial Government for the 2019-2023 Period Using a Financial Ratio Approach - Panjaitan, Enrico Paul Anggiat; Haliah, Haliah (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
This research aims to evaluate the financial performance of the South Sulawesi Region from 2019 to 2023. This research employs quantitative descriptive approach. The data collected using documentation method, the analyzed data is secondary data obtained from the Financial Reports of South Sulawesi Province. The analysis is based on five financial ratios: the independence ratio, the fiscal decentralization ratio, the regional original revenue (PAD) effectiveness ratio, the efficiency ratio, and the growth ratio. The findings reveal that the independence ratio indicates that South Sulawesi has achieved financial independence since 2022. The fiscal decentralization ratio has shown favorable outcomes since 2019. The PAD effectiveness ratio is categorized as neutral, while the regional efficiency ratio suggests inefficiency. Meanwhile, the growth ratio reflects a positive trend in regional financial growth after the COVID-19 pandemic.